2020
DOI: 10.1038/s41598-020-71548-z
|View full text |Cite|
|
Sign up to set email alerts
|

Development of humanized mouse and rat models with full-thickness human skin and autologous immune cells

Abstract: The human skin is a significant barrier for protection against pathogen transmission. Rodent models used to investigate human-specific pathogens that target the skin are generated by introducing human skin grafts to immunocompromised rodent strains. Infection-induced immunopathogenesis has been separately studied in humanized rodent models developed with human lymphoid tissue and hematopoietic stem cell transplants. Successful co-engraftment of human skin, autologous lymphoid tissues, and autologous immune cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Perhaps due to its critical role in various bodily functions, diseases of the skin are common, with >5.4 million cases of skin cancer every year and ~500,000 patients who receive treatment for burns or other skin trauma [6][7][8][9][10][11] . The mouse is a standard model for investigating skin development and disease in vivo [12][13][14][15][16][17] . Yet, there are critical differences between mouse and human skin, such as the mechanisms of wound closure, which have confounded efforts to translate therapies to the clinic 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps due to its critical role in various bodily functions, diseases of the skin are common, with >5.4 million cases of skin cancer every year and ~500,000 patients who receive treatment for burns or other skin trauma [6][7][8][9][10][11] . The mouse is a standard model for investigating skin development and disease in vivo [12][13][14][15][16][17] . Yet, there are critical differences between mouse and human skin, such as the mechanisms of wound closure, which have confounded efforts to translate therapies to the clinic 18 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies primarily attempt to generate humanized rat models of various pathological conditions and tissue damage without using BC methods. With the emergence of new humanized rat models, the future of functional human-rat interspecies chimerism holds excellent promise, while the permissiveness of non-cancerous, normal human epithelial chimerism needs to be addressed well ( Agarwal et al, 2020 ).…”
Section: Interspecies Barriers In Chimerasmentioning
confidence: 99%
“…Such models can be definitely a boon to study the immunomodulation in skin wound environments. 156 Hu et al developed an improvised humanized mouse model using a double transgenic mouse and fluorescence imaging to study the accurate healing time of wounds. They observed that macroscopic evaluation of wound showed a delay of 2 days in normal light as compared to fluorescent light and hence over estimation of wound closure time.…”
Section: Current Approaches Towards Wound Regenerationmentioning
confidence: 99%